{“When Grief Breaks Your Heart”: A Case Study of Interpersonal Psychotherapy Delivered in a Primary Care Setting} - Gomes, M.F.; Chowdhary, N.; Vousoura, E.; Verdeli, H. (Journal of Clinical Psychology, 2016)
© 2016 Wiley Periodicals, Inc. Depression and anxiety, the so-called common mental disorders (CMDs), are highly prevalent and disabling, yet remain largely untreated. This treatment gap is particularly true in low- and middle-income settings, where there is significant scarcity of resources (including human resources) and treatment accessibility is complicated by stigma surrounding mental illness. To address these challenges, the MANAS trial, one of the largest to date randomized, controlled trials, aimed to test the effectiveness of a stepped care intervention led by lay health counselors in primary care settings in Goa, India. Six- and 12-month follow-up outcomes suggest that MANAS was a safe, feasible, effective, and cost-effective intervention for CMDs in that context. This article demonstrates the use of culturally adapted IPT as an intervention to treat CMDs in a 54-year-old Indian primary care patient struggling with depression and heart-related problems after his wife's death. A case formulation is presented based on core IPT principles, followed by detailed delineation of treatment from beginning through termination.
Keywords: global mental health; India; Interpersonal psychotherapy; primary care; stepped care interventions